Aktivitas Antioksidan Fraksi Air dan Etil Asetat dari Ekstrak Sarang Semut (Myrmecodia pendens Merr. & Perry) - Suprijono, Agus; Hesti Wulan S, A. Ariani; Dyah Pratiwi, Arini (Jurnal Farmasi (Journal of Pharmacy), 2022)
Sarang Semut (Myrmecodia pendens Merr. & Perry) is a medicinal herbal contains of flavonoids, tannins, phenolic compounds, polyphenols, and vitamin E. Those substances are potent antioxidants. This research refers to previous research that the ethanol extract of Sarang Semut (Myrmecodia pendens Merr. & Perry) provided antioxidant activity with a mean EC50 of 3.8021 µg/ml. The purpose of this research was to determine the antioxidant activity of the fracti ons of ethanolic extract of Sarang Semut (Myrmecodia pendens Merr. & Perry) and to determine the highest antioxidant activity of them expressed by EC50. The ethanol extract of Sarang Semut (Myrmecodia pendens Merr. & Perry) was obtained by filtration using the soxletation method with 96% ethanol as solvent, then the ethanolic extract partitioned by liquid-liquid fractionation with water and ethyl acetate. Each fraction at a concentration of 0.9 µg/ml, 1.0 µg/ml, 2.0 µg/ml, 3.0 µg/ml, 4.0 µg/ml, and 5.0 µg/ml were tested by the DPPH method (1,1-diphenyl-2-picrylhidrazyl 2) using a spectrophotometer at λ 515 nm and operating time 35 minutes. The result shows the fraction of ethyl acetate has the highest antioxidant activity with a mean EC50 of 2.8821+ 0.1361 µg/ml. While the average EC50 fraction of water is 3.8830 + 0.2205 µg/ml. From the statistical t test is known that the fraction of water and ethyl acetate have significantly different rates of EC50.